Strategies utilised to introduce a Caribbean Examinations Council - Bailey, Barbara
The decision to establish a Caribbean Examinations Council (CXC) was taken at the 1964 Conference of Heads of Governments of the Commonwealth Caribbean. This Council was to be charged with the responsibility of developing and introducing a system of examination for candidates who had completed five years of secondary education. This paper discusses the strategies adopted in the establishment of the CXC
Keywords: Caribbean Examinations Council